2002
DOI: 10.1210/jcem.87.6.8599
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemic Clamp Assessment of Insulin Secretory Responses in Normal Subjects Treated with Olanzapine, Risperidone, or Placebo

Abstract: The goal of this study was to evaluate the effect of olanzapine or risperidone treatment on beta-cell function in healthy volunteers. Subjects were randomly assigned to single-blind therapy with olanzapine (10 mg/d; n = 17), risperidone (4 mg/d; n = 13), or placebo (n = 18) for 15-17 d. Insulin secretion was quantitatively assessed at baseline and the end of the study period using the hyperglycemic clamp. Weight increased significantly (P < 0.01) in the olanzapine (2.8 +/- 1.7 kg) and risperidone (3.1 +/- 2.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 35 publications
4
40
2
2
Order By: Relevance
“…In contrast to previous reports (Sowell et al, 2002(Sowell et al, , 2003 our clamp experiments show that there is a significant decrease (po0.001) in whole body insulin sensitivity in response to hyperinsulinemic euglycemic challenge in healthy subjects (baseline: 5.7±0.4 ml/h/kg, mean ± SM) following oral intake of 10 mg/day olanzapine (4.7 ± 0.3 ml/h/kg, mean ± SM, Figure 1). Whereas Sowell et al reported an increased total insulin response for olanzapine, they attributed those changes to the antipsychotic-induced weight gain and concluded that the observed changes were insignificant (Sowell et al, 2002).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous reports (Sowell et al, 2002(Sowell et al, , 2003 our clamp experiments show that there is a significant decrease (po0.001) in whole body insulin sensitivity in response to hyperinsulinemic euglycemic challenge in healthy subjects (baseline: 5.7±0.4 ml/h/kg, mean ± SM) following oral intake of 10 mg/day olanzapine (4.7 ± 0.3 ml/h/kg, mean ± SM, Figure 1). Whereas Sowell et al reported an increased total insulin response for olanzapine, they attributed those changes to the antipsychotic-induced weight gain and concluded that the observed changes were insignificant (Sowell et al, 2002).…”
Section: Discussioncontrasting
confidence: 99%
“…Sowell et al (2002) performed hyperglycemic clamps in healthy subjects before and after 3 weeks of oral intake of olanzapine, risperidone or placebo. Despite their finding of substantial weight gain that was reported for olanzapine and risperidone (B1.5 kg), they did not find the observed changes in whole body insulin sensitivity to be significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where a change in insulin resistance has been observed in humans, this has been entirely explicable by a change in body weight [69,70]. However, studies in myotubes have shown that olanzapine inhibits insulin signalling [71].…”
Section: Plausibilitymentioning
confidence: 99%
“…Experiments in islet cell cultures have shown that clozapine and olanzapine, but not quetiapine, risperidone and ziprasidone, increase insulin release [75]. It is unclear how these findings are to be interpreted during normal physiology as no change in beta cell function has been observed in humans [70]. Nevertheless there are case reports of diabetic ketoacidosis in patients receiving antipsychotics [67].…”
Section: Plausibilitymentioning
confidence: 99%